(untitled) (SCIÉNDO INGENIUM, 2022)
The research is related to the field of knowledge, considering research, development and innovation (R+D+i), using tools of Technological Surveillance and Competitive Intelligence (VT-IC), with the objective of determining an improvement proposal for research lines in university education. The work of descriptive design and cross-sectional, presents a mixed approach; analyzing qualities and academic research needs through expert judgment. The methodology used literature reviews and consultation of scientific databases to propose a VT-IC model. The results of the model were evaluated in two interactions (Delphi Method) ending with a rating of very good in 80%. Conclusions: The application of VT-IC model required an internal and external analysis, considering needs, problems, research areas and above all the experience of researchers, allowing new paradigms and approaches linked to educational processes and new areas of research, experts consider applicable, allowing automation and new mechanisms to search for information that allows decision making, rethinking research areas, professional competencies, new lines of research and future trends for an organizational alignment, oriented to a disruptive design approach to the generation of intelligent curricula.